Karzeł na cesarskim tronie. „Relacja z poselstwa do Konstantynopola” Liudpranda z Cremony (1–12; 39–42): wstęp, przekład, komentarz - Ptak, Karolina (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2024)
The paper contains a translation of selected excerpts from The Embassy to Constantinople by Liudprand of Cremona. The work of Liudprand was created in the mid-tenth century and is considered a unique document of medieval diplomacy. Selected excerpts present the Byzantine emperor Nikephoros II Phokas. The thesis consists of two parts: introduction and translation with a commentary. The introduction contains information about the author of “The Embassy” and the context of writing, as well as the language and literary style.